The Mediating Effect of Job Expectations on Selected Human Resource Management Practices and Career Satisfaction - Mata, Love Joy A.; Abueg, Madelaine I.; Alano, Melody O.; Delantar, Zena Jean A.; Malabad, Angelica Louise C.; Nuevas, Angela May A.; Reyes, Rhea Joyce A.; Socao, Jesselle Maine R.; Lipio, Eloisa Mae P. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
As companies face changes from globalization, new technologies, and a younger workforce, Human Resource Management (HRM) has become more important in keeping employees satisfied and motivated. This study looked into how HRM practices and job expectations affect the career satisfaction of Generation Z alumni. The researchers used a descriptive quantitative method with 91 participants. The data were analyzed using frequency counts, mean, standard deviation, and Pearson correlation. The results showed that HRM practices have a strong and direct effect on career satisfaction. While job expectations also had a positive connection with satisfaction, they did not serve as a link between HRM practices and satisfaction. This means that HR practices alone can already help increase how satisfied employees feel in their careers. Based on the findings, organizations can focus on improving HR practices such as fair salary, open communication, giving feedback, and providing training or growth opportunities. These can make employees feel valued and more engaged at work. The study also suggests that HR planning should support not just work performance but also overall employee well-being.